2013
DOI: 10.1039/c3cp52559g
|View full text |Cite
|
Sign up to set email alerts
|

A new hole density as a stability measure for boron fullerenes

Abstract: We investigate the stability of boron fullerene sets B76, B78 and B82. We evaluate the ground state energies, nucleus-independent chemical shift (NICS), the binding energies per atom and the band gap values by means of first-principles methods. We construct our fullerene design by capping of pentagons and hexagons of B60 cage in such a way that the total number of atoms is preserved. In doing so, a new hole density definition is proposed such that each member of a fullerene group has a different hole density w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
(89 reference statements)
1
11
0
Order By: Relevance
“…Our previous benchmark calculations showed that both PBE and PBE0 are able to distinguish the structural isomers of B 20 and give the correct energy order of the eight isomers compared to CCSD(T)/6-311G* results 34 . Vibrational analysis of these cluster isomers in their equilibrium configurations has also been carried out at the PBE0/6-311+G(d) level of theory to ensure that there are no imaginary frequencies corresponding to the saddle points on the PES.…”
Section: Units and Prevails Over The Competing Structural Isomers Sucmentioning
confidence: 99%
“…Our previous benchmark calculations showed that both PBE and PBE0 are able to distinguish the structural isomers of B 20 and give the correct energy order of the eight isomers compared to CCSD(T)/6-311G* results 34 . Vibrational analysis of these cluster isomers in their equilibrium configurations has also been carried out at the PBE0/6-311+G(d) level of theory to ensure that there are no imaginary frequencies corresponding to the saddle points on the PES.…”
Section: Units and Prevails Over The Competing Structural Isomers Sucmentioning
confidence: 99%
“…As the nearest neighbor of carbon in the periodic table, all boron fullerene analogues have been pursued in the past few years since the pioneering theoretical prediction of the B 80 cage in 2007. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] However, evidence for boron fullerenes is scarce. Recent studies have revealed that core-shell structures are more energetically favorable in the size range with n Z 68.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these double-chain ribbons with different lengths have the similar aromaticity. Obviously, the average NICS(1) values (from -8.9 to -11.4 ppm) of these doublechain B 2n C 2 H 2 are more than those of the medium-sized boron cages (from -22.1 to -55.3 ppm) [34][35][36][37] so that their aromaticity is generally less than those of boron cages interwoven by the double-chains.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the B 40 -/0 and B 39 -fullerenes are composed of interwoven boron double-chain ribbons. Furthermore, many similar medium-sized boron cages have been proposed from the first principle methods [34][35][36][37][38]. On the other hand, the free-standing and metalsupported two-dimensional boron sheets are predicted to be mainly composed of interwoven double-chain ribbons [39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%